2016
DOI: 10.4236/ojpm.2016.611024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Women’s Autonomy and Male Involvement on Reproductive and Child Health (RCH) Service Utilization in Uttar Pradesh

Abstract: Introduction: Effective utilization of reproductive and child health (RCH) services is important to reduce morbidity and mortality among mothers as well as children under-five. After International Conference on Population and Development (ICPD), 1994 India has increasingly integrated male participation in women's reproductive health to improve the women's health care during pregnancy and child birth. This study examined effect of women's autonomy and male involvement on RCH services utilization in Uttar Prades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…Existing studies from developing countries have shown that women's autonomy in health care decisions is related to child's health, women's health, utilization of healthcare services and empowerment amongst others [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies from developing countries have shown that women's autonomy in health care decisions is related to child's health, women's health, utilization of healthcare services and empowerment amongst others [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Alemayehu and Meskele [2] noted that the ability of a woman to visit health care facilities and receive treatment is somewhat dependent on their ability to take personal decisions. However, societal norms, culture, gender roles, gender inequality, religious norms and other socio-cultural factors influence the way women live their lives in developing countries [3].Existing studies from developing countries have shown that women's autonomy in health care decisions is related to child's health, women's health, utilization of healthcare services and empowerment amongst others [4][5][6][7][8][9].Similarly, higher risk of malnutrition has been observed from households where women had little or no autonomy in making household decisions [10]. The ability of women to take health care decision has also been reported in literature to improve the survival rates of their children [11][12][13][14].…”
mentioning
confidence: 99%
“…The most interesting finding was that husbands accompanying their wives to antenatal visits and the autonomy of study participants were the only two significant independent factors related to four or more ANC visits after adjusting for other significant factors. Sahu et al secondary data analysis of NFHS 3 (2005NFHS 3 ( -2006 reported that greater spousal involvement and women's decision-making autonomy were associated with the utilization of full antenatal care services 25) . Similar findings related to husbands' involvement were reported by Mohammad et al and Redshaw et al 26,27) The involvement of husbands during antenatal visits has become an important factor for ANC visits, as their knowledge regarding various health issues during pregnancy would improve and could further motivate wives to utilize antenatal care services.…”
Section: Discussionmentioning
confidence: 99%
“…Certain aspects of MI such as communication, decision making and 'feeling supported' were rarely included as MI indicators (10.64%, 8.51% and 6.38%, respectively) in the studies included in our review, while both quantitative and qualitative research have shown that these aspects of men's involvement play an important role in maternal health care access, utilisation and outcomes. [37][38][39][40][41][42] The narrow focus on specific actions of men (such as financial support and ANC attendance) without taking into other aspects (such as couple dynamics and gender equality) clearly entails a risk of missing essential information and underreporting negative consequences. The need for greater incorporation of gender-transformative conceptual approaches into MI interventions, with effective measures, was already emphasised by Comrie-Thomson et al 13 Another recent systematic review reported that worldwide only a minority of the interventions aiming at engaging men and boys in sexual reproductive health and rights (SRHR) includes a gender transformative approach.…”
Section: Discussionmentioning
confidence: 99%